A glass fiber reinforced composite plastic and a method for producing the same
Patent Information
- Application Number
- CN202510801394.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-16
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-06-16
AI Technical Summary
然而,传统的PBT/PC合金制备和应用时,如制备电子产品外壳、支架、按键等产品时,由于PBT为结晶性聚合物,PC为非晶态聚合物,形成典型的结晶与非晶聚合物共混体系,两者极性差异导致其界面粘结不良,易发生相分离,限制了力学性能的提高,且耐磨性不好,在长期使用易因摩擦产生划痕或磨损并常存在耐水解性和耐化学性不佳的问题,对产品外观和使用寿命造成不良影响,有待于进一步改进
[0018]双螺杆挤出机各区的温度分别为:所述挤出机为双螺杆挤出机,双螺杆挤出机各区的温度为:一区温度:220-230℃,二区温度:230-240℃,三区温度:230-240℃,四区温度:240-250℃,五区温度:235-245℃,机头温度:235-245℃,所述侧喂料口设在四区;所述双螺杆挤出机的螺杆转速为150-300rpm。
Smart Images

Figure BDA0005451350570000071
Abstract
Description
Technical Field
[0001] This invention relates to the field of plastics technology, and more specifically to a glass fiber reinforced composite plastic and its preparation method. Background Technology
[0002] PC / PBT composites are plastic alloys made by blending polycarbonate (PC) and polybutylene terephthalate (PBT). Due to their combination of PBT's chemical resistance and processing fluidity with PC's high toughness and heat resistance, PBT / PC composites have been widely used in electronics, automotive, and industrial machinery. However, in the traditional preparation and application of PBT / PC alloys, such as in the manufacture of electronic product casings, brackets, and buttons, the polarity difference between PBT (a crystalline polymer) and PC (an amorphous polymer) results in a typical blend system of crystalline and amorphous polymers. This leads to poor interfacial bonding and phase separation, limiting the improvement of mechanical properties. Furthermore, poor wear resistance makes them prone to scratches and wear during long-term use, and they often exhibit poor hydrolysis and chemical resistance, negatively impacting product appearance and lifespan. Further improvements are needed. Summary of the Invention
[0003] The purpose of this invention is to overcome the shortcomings of the prior art by providing a glass fiber reinforced composite plastic, which has good mechanical properties, chemical resistance and wear resistance.
[0004] Another objective of this invention is to provide a method for preparing glass fiber reinforced composite plastics, wherein the preparation method is stable, easy to control, has high production efficiency, and is conducive to industrial production.
[0005] The objective of this invention is achieved through the following technical solution: a glass fiber reinforced composite plastic, comprising the following raw materials in parts by weight: 55-65 parts PBT, 30-40 parts PC, 25-35 parts glass fiber, 10-15 parts polyethylene 2,5-furandicarboxylate, 5-10 parts compatibilizer, 4-10 parts maleic anhydride-grafted polyolefin elastomer, 3-8 parts silane coupling agent, 2-6 parts antioxidant, 1-5 parts lubricant, and 5-12 parts synergistic agent.
[0006] The glass fiber reinforced composite plastic of the present invention uses PBT, PC and polyethylene 2,5-furandicarboxylate as the matrix plastic. The interaction between polyethylene 2,5-furandicarboxylate and the polar groups of PBT and PC improves their compatibility and endows the composite material with good strength and toughness. By adding glass fiber and silane coupling agent, the composite material can be reinforced and well coordinated with compatibilizers, maleic anhydride-grafted polyolefin elastomers, synergistic agents, etc. The synergistic effect of each raw material gives the glass fiber reinforced composite plastic good mechanical properties, chemical resistance and wear resistance.
[0007] Furthermore, the silane coupling agent is at least one selected from vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-aminopropyltriethoxysilane.
[0008] Furthermore, the antioxidant is at least one of hindered phenolic antioxidants and phosphite antioxidants.
[0009] Furthermore, the antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1.5-4:1.
[0010] Furthermore, the lubricant is at least one selected from calcium stearate, magnesium stearate, zinc stearate, silicone powder, polyethylene wax, and oxidized polyethylene wax.
[0011] Furthermore, each part of the synergistic agent comprises the following raw materials in parts by weight: 3-5 parts magnesium sulfate whiskers, 2-4 parts hyperbranched polyester, and 1-3 parts polycarbodiimide. This invention, by compounding the above raw materials to form a synergistic agent and adding it to the composite material system, helps to enhance the toughness, strength, and wear resistance of the composite material, and improves its hydrolysis resistance and chemical corrosion resistance.
[0012] Furthermore, the preparation method of each part of the compatibilizer includes the following steps: taking 60-70 parts of dried PBT, 30-40 parts of PC, 0.5-1.5 parts of antioxidant, 0.5-1 part of lubricant, 1-2 parts of chain extender, and 0.1-0.3 parts of catalyst by weight, mixing them, blending them in an extruder, and granulating them to obtain the compatibilizer. The extruder is a twin-screw extruder.
[0013] Furthermore, in the preparation method of the compatibilizer, the antioxidant is at least one of hindered phenolic antioxidants and phosphite antioxidants; the lubricant is at least one of calcium stearate, magnesium stearate, zinc stearate, silicone powder, polyethylene wax, and oxidized polyethylene wax.
[0014] Furthermore, in the method for preparing the compatibilizer, the catalyst is at least one of tetrabutyl titanate, tetraisopropyl titanate, and dibutyltin dilaurate.
[0015] Furthermore, in the method for preparing the compatibilizer, the extruder is a twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are as follows: Zone 1: 215-225℃, Zone 2: 230-240℃, Zone 3: 235-245℃, Zone 4: 240-250℃, Zone 5: 240-250℃, and Die head temperature: 240-250℃; the screw speed of the twin-screw extruder is 200-400 rpm.
[0016] The present invention obtains a compatibilizer by using the above-mentioned raw materials and preparation method. The PBT / PC segments in the compatibilizer can achieve good compatibility with the matrix resin and good coordination with other raw materials, which is beneficial to improving the mechanical properties and durability of the composite material.
[0017] Another object of the present invention is to provide a method for preparing glass fiber reinforced composite plastic, comprising the following steps: mixing raw materials other than glass fiber and silane coupling agent in proportion; adding the mixed raw materials into an extruder through the main feed port; adding glass fiber pretreated with silane coupling agent into the extruder through the side feed port; performing melt blending and granulation to obtain glass fiber reinforced composite plastic.
[0018] The temperatures of each zone of the twin-screw extruder are as follows: Zone 1: 220-230℃, Zone 2: 230-240℃, Zone 3: 230-240℃, Zone 4: 240-250℃, Zone 5: 235-245℃, and the die head temperature is 235-245℃. The side feed port is located in Zone 4. The screw speed of the twin-screw extruder is 150-300 rpm.
[0019] The beneficial effects of this invention are as follows: The glass fiber reinforced composite plastic of this invention uses a compound of PBT, PC, and polyethylene 2,5-furandicarboxylate as the matrix plastic, reinforced with glass fiber, and synergistically reacts with compatibilizers, maleic anhydride-grafted polyolefin elastomers, and synergistic additives to produce a glass fiber reinforced composite plastic with excellent mechanical properties, chemical resistance, and wear resistance. The preparation method of the glass fiber reinforced composite plastic is stable, easy to control, and has high production efficiency, which is conducive to industrial production. Detailed Implementation
[0020] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to embodiments. The content mentioned in the embodiments is not intended to limit the present invention.
[0021] In some embodiments of the present invention, a glass fiber reinforced composite plastic comprises the following raw materials in parts by weight: 55-65 parts PBT, 30-40 parts PC, 25-35 parts glass fiber, 10-15 parts polyethylene 2,5-furandicarboxylate, 5-10 parts compatibilizer, 4-10 parts maleic anhydride-grafted polyolefin elastomer, 3-8 parts silane coupling agent, 2-6 parts antioxidant, 1-5 parts lubricant, and 5-12 parts synergistic agent.
[0022] In some embodiments of the present invention, the silane coupling agent is at least one selected from vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-aminopropyltriethoxysilane. The glass fiber is alkali-free chopped glass fiber with a length of 3-5 mm.
[0023] In some embodiments of the present invention, the antioxidant is at least one of hindered phenolic antioxidants and phosphite antioxidants.
[0024] In some embodiments of the present invention, the antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1.5-4:1.
[0025] In some embodiments of the present invention, the lubricant is at least one of calcium stearate, magnesium stearate, zinc stearate, silicone powder, polyethylene wax, and oxidized polyethylene wax.
[0026] In some embodiments of the present invention, the lubricant is composed of calcium stearate and silicone powder in a mass ratio of 1-2:1-2.
[0027] In some embodiments of the present invention, each part of the synergist comprises the following raw materials in parts by weight: 3-5 parts magnesium sulfate whiskers, 2-4 parts hyperbranched polyester, and 1-3 parts polycarbodiimide.
[0028] In some embodiments of the present invention, the preparation method of each part of the compatibilizer includes the following steps: taking 60-70 parts of dried PBT, 30-40 parts of PC, 0.5-1.5 parts of antioxidant, 0.5-1 part of lubricant, 1-2 parts of chain extender, and 0.1-0.3 parts of catalyst by weight, mixing them, blending them in an extruder, and granulating them to obtain the compatibilizer. The extruder is a twin-screw extruder.
[0029] In some embodiments of the present invention, in the method for preparing the compatibilizer, the antioxidant is at least one of hindered phenolic antioxidants and phosphite antioxidants; the lubricant is at least one of calcium stearate, magnesium stearate, zinc stearate, silicone powder, polyethylene wax and oxidized polyethylene wax.
[0030] In some embodiments of the present invention, in the method for preparing the compatibilizer, the chain extender is at least one of 2,2'-bis(2-oxazoline) and epoxy chain extenders; the catalyst is at least one of tetrabutyl titanate, tetraisopropyl titanate and dibutyltin dilaurate.
[0031] In some embodiments of the present invention, in the method for preparing the compatibilizer, the extruder is a twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are: Zone 1: 215-225℃, Zone 2: 230-240℃, Zone 3: 235-245℃, Zone 4: 240-250℃, Zone 5: 240-250℃, and Die head temperature: 240-250℃; the screw speed of the twin-screw extruder is 200-400 rpm.
[0032] In some embodiments of the present invention, a method for preparing a glass fiber reinforced composite plastic includes the following steps: mixing raw materials other than glass fiber and silane coupling agent in proportion; adding the mixed raw materials into an extruder from the main feed port; adding glass fiber pretreated with silane coupling agent into the extruder from the side feed port; performing melt blending and granulation to obtain a glass fiber reinforced composite plastic.
[0033] In some embodiments of the present invention, the method for treating glass fibers with silane coupling agent includes the following steps: taking 3-8 parts by weight of silane coupling agent and 100 parts by weight of 20-25 wt% ethanol aqueous solution, mixing them evenly, adjusting the pH to 5-6, then adding 25-35 parts of glass fiber and impregnating for 20-40 minutes, and drying for later use.
[0034] In some embodiments of the present invention, the extruder is a twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are as follows: Zone 1: 220-230℃, Zone 2: 230-240℃, Zone 3: 230-240℃, Zone 4: 240-250℃, Zone 5: 235-245℃, and the die head temperature: 235-245℃. The side feed port is located in Zone 4. The screw speed of the twin-screw extruder is 150-300 rpm.
[0035] Example 1
[0036] This embodiment provides a glass fiber reinforced composite plastic, comprising the following raw materials in parts by weight: 60 parts PBT, 35 parts PC, 31 parts glass fiber, 12 parts polyethylene 2,5-furandicarboxylate, 7 parts compatibilizer, 6 parts maleic anhydride-grafted polyolefin elastomer, 5 parts silane coupling agent, 4 parts antioxidant, 3 parts lubricant, and 10 parts synergist. The PBT used is SABIC VALOX325E PBT. The PC used is Shandong Lihua Yiweiyuan WY-111BR. The maleic anhydride-grafted polyolefin elastomer used is Dow Chemical GR216 maleic anhydride-grafted polyolefin elastomer. The polyethylene 2,5-furandicarboxylate used is Hubei Jiufenglong Chemical polyethylene 2,5-furandicarboxylate. The glass fiber is alkali-free chopped glass fiber with a length of 3-5 mm. The PBT, PC, polyethylene 2,5-furandicarboxylate, and glass fiber are pre-dried before use.
[0037] Furthermore, the silane coupling agent is composed of vinyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane in a weight ratio of 3:2.
[0038] Furthermore, the antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1.5:1.
[0039] Furthermore, the lubricant is composed of calcium stearate and silicone powder in a mass ratio of 1:1.
[0040] Furthermore, each part of the synergistic agent comprises the following raw materials in parts by weight: 4.5 parts magnesium sulfate whiskers, 3.5 parts hyperbranched polyester, and 2 parts polycarbodiimide. The aspect ratio of the magnesium sulfate whiskers is 50-60:1. The polycarbodiimide is Rhein Chemicals' Stabaxol P polycarbodiimide. The hyperbranched polyester is Wuhan Hyperbranched Resin Technology's HyPer H20 hyperbranched polyester.
[0041] Furthermore, the preparation method of each compatibilizer includes the following steps: taking 65 parts of dried PBT, 35 parts of PC, 1 part of antioxidant, 0.8 parts of lubricant, 1.5 parts of chain extender, and 0.15 parts of catalyst by weight, mixing them, blending them in an extruder, and granulating them to obtain the compatibilizer; the chain extender is BASF ADR-4370 chain extender, the catalyst is tetrabutyl titanate, the antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1.5:1; the lubricant is composed of calcium stearate and silicone powder in a mass ratio of 1:1.
[0042] Furthermore, in the preparation method of the compatibilizer, the temperatures of each zone of the twin-screw extruder are as follows: Zone 1: 220℃, Zone 2: 235℃, Zone 3: 240℃, Zone 4: 245℃, Zone 5: 245℃, and Die head: 245℃; the screw speed of the twin-screw extruder is 300 rpm.
[0043] This embodiment also provides a method for preparing glass fiber reinforced composite plastic, including the following steps: mixing raw materials other than glass fiber and silane coupling agent in proportion, adding the mixed raw materials into the extruder from the main feed port, and then adding glass fiber pretreated with silane coupling agent into the extruder from the side feed port, performing melt blending and granulation to obtain glass fiber reinforced composite plastic.
[0044] Furthermore, the method for treating glass fibers with silane coupling agent includes the following steps: 5 parts by weight of silane coupling agent and 100 parts by weight of 20wt% ethanol aqueous solution are mixed evenly, the pH is adjusted to 5.5, and then 28 parts of glass fiber are added and impregnated for 30 minutes. After drying, it is ready for use.
[0045] Furthermore, the extruder is a twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are as follows: Zone 1: 225℃, Zone 2: 235℃, Zone 3: 235℃, Zone 4: 245℃, Zone 5: 240℃, and the die head temperature: 240℃. The side feed port is located in Zone 4. The screw speed of the twin-screw extruder is 250 rpm.
[0046] Example 2
[0047] This embodiment provides a glass fiber reinforced composite plastic, comprising the following raw materials in parts by weight: 60 parts PBT, 35 parts PC, 31 parts glass fiber, 14 parts polyethylene 2,5-furandicarboxylate, 9 parts compatibilizer, 6 parts maleic anhydride-grafted polyolefin elastomer, 5 parts silane coupling agent, 4 parts antioxidant, 3 parts lubricant, and 11 parts synergistic agent.
[0048] Furthermore, the silane coupling agent is composed of vinyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane in a weight ratio of 3:2.
[0049] Furthermore, each part of the synergistic agent comprises the following raw materials in parts by weight: 5 parts magnesium sulfate whiskers, 4 parts hyperbranched polyester, and 2 parts polycarbodiimide.
[0050] This embodiment also provides a method for preparing glass fiber reinforced composite plastic, including the following steps: mixing raw materials other than glass fiber and silane coupling agent in proportion, adding the mixed raw materials into the extruder from the main feed port, and then adding glass fiber pretreated with silane coupling agent into the extruder from the side feed port, performing melt blending and granulation to obtain glass fiber reinforced composite plastic.
[0051] Furthermore, the method for treating glass fibers with silane coupling agents includes the following steps:
[0052] Furthermore, the extruder is a twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are as follows: Zone 1: 225℃, Zone 2: 235℃, Zone 3: 235℃, Zone 4: 240℃, Zone 5: 240℃, and the die head temperature: 240℃. The side feed port is located in Zone 4. The screw speed of the twin-screw extruder is 250 rpm.
[0053] The rest of the content of this embodiment is the same as that of Embodiment 1, and will not be repeated here.
[0054] Example 3
[0055] This embodiment provides a glass fiber reinforced composite plastic, comprising the following raw materials in parts by weight: 60 parts PBT, 35 parts PC, 31 parts glass fiber, 10 parts polyethylene 2,5-furandicarboxylate, 5 parts compatibilizer, 6 parts maleic anhydride-grafted polyolefin elastomer, 5 parts silane coupling agent, 4 parts antioxidant, 3 parts lubricant, and 8 parts synergistic agent.
[0056] Furthermore, the silane coupling agent is composed of vinyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane in a weight ratio of 3:2.
[0057] Furthermore, each part of the synergistic agent comprises the following raw materials in parts by weight: 3.5 parts magnesium sulfate whiskers, 2.5 parts hyperbranched polyester, and 2 parts polycarbodiimide.
[0058] This embodiment also provides a method for preparing glass fiber reinforced composite plastic, including the following steps: mixing raw materials other than glass fiber and silane coupling agent in proportion, adding the mixed raw materials into the extruder from the main feed port, and then adding glass fiber pretreated with silane coupling agent into the extruder from the side feed port, performing melt blending and granulation to obtain glass fiber reinforced composite plastic.
[0059] Furthermore, the extruder is a twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are as follows: Zone 1: 225℃, Zone 2: 235℃, Zone 3: 235℃, Zone 4: 245℃, Zone 5: 240℃, and the die head temperature: 240℃. The side feed port is located in Zone 4. The screw speed of the twin-screw extruder is 250 rpm.
[0060] The rest of the content of this embodiment is the same as that of Embodiment 1, and will not be repeated here.
[0061] Comparative Example 1
[0062] The difference between this comparative example and Example 1 is that the glass fiber reinforced composite plastic in this comparative example does not contain synergistic additives.
[0063] Comparative Example 2
[0064] The difference between this comparative example and Example 1 is that the glass fiber reinforced composite plastic in this comparative example does not contain a compatibilizer, and is replaced by an equal amount of PBT and PC mixture. The mass ratio of PBT to PC in the composite plastic of this comparative example is the same as that in Example 1.
[0065] Comparative Example 3
[0066] The difference between this comparative example and Example 1 is that the glass fiber reinforced composite plastic in this comparative example does not contain polyethylene 2,5-furandicarboxylate, but is replaced by an equal amount of PBT and PC mixture. The mass ratio of PBT to PC in the composite plastic of this comparative example is the same as that in Example 1.
[0067] The plastic granules obtained in Examples 1-3 and Comparative Examples 1-3 were dried and then injection molded to prepare specimens with dimensions of 80 mm × 10 mm × 4 mm. Performance tests were performed on the specimens obtained in Examples 1-3 and Comparative Examples 1-2, and the test results are shown in Table 1 below.
[0068]
[0069] Tensile strength was tested according to GB / T 1040.2-2022. Flexural strength was tested according to GB / T 9341-2008. Cantilever beam notched impact strength was tested according to GB / T 1843-2008. Abrasion resistance was tested according to ASTM D4060, using a Taber abrasion tester with a CS-10 wheel and a 1000g load, calculating the mass loss after 1000 cycles. Chemical resistance was tested according to GB / T 3857-2017, immersing the sample in 5% hydrochloric acid at 23°C for 168 hours, and testing the retention rate of tensile strength. The flame retardancy rating of Examples 1-3 and Comparative Examples 1-2 is UL94 V-0.
[0070] In summary, the glass fiber reinforced composite plastic of the present invention uses a compound of PBT, PC, and polyethylene 2,5-furandicarboxylate as the matrix plastic, reinforced with glass fiber, and achieves good synergy with compatibilizers, maleic anhydride-grafted polyolefin elastomers, and synergistic additives. The synergistic effect of these raw materials results in a glass fiber reinforced composite plastic with excellent mechanical properties, chemical resistance, and wear resistance, making it suitable for manufacturing products such as keycaps for electronic products. The preparation method of the glass fiber reinforced composite plastic is stable, easy to control, and has high production efficiency, which is conducive to industrial production.
[0071] The specific embodiments described above are further illustrations of the technical solution and beneficial effects of the present invention, and are not intended to limit the implementation methods. For those skilled in the art, any obvious substitutions without departing from the concept of the present invention are within the protection scope of the present invention.
Claims
1. A glass fiber reinforced composite plastic, characterized in that: The raw materials include the following parts by weight: 55-65 parts PBT, 30-40 parts PC, 25-35 parts glass fiber, 10-15 parts polyethylene 2,5-furandicarboxylate, 5-10 parts compatibilizer, 4-10 parts maleic anhydride-grafted polyolefin elastomer, 3-8 parts silane coupling agent, 2-6 parts antioxidant, 1-5 parts lubricant, and 5-12 parts synergist. The preparation method for each part of the compatibilizer includes the following steps: 60-70 parts dried PBT, 30-40 parts PC, 0.5-1.5 parts antioxidant, 0.5-1 part lubricant, 1-2 parts chain extender, and 0.1-0.3 parts catalyst are mixed according to their weight, blended in an extruder, and granulated to obtain the compatibilizer.
2. The glass fiber reinforced composite plastic according to claim 1, characterized in that: The silane coupling agent is at least one selected from vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-aminopropyltriethoxysilane.
3. The glass fiber reinforced composite plastic according to claim 1, characterized in that: The antioxidant is at least one of hindered phenolic antioxidants and phosphite antioxidants.
4. The glass fiber reinforced composite plastic according to claim 1, characterized in that: The lubricant is at least one of calcium stearate, magnesium stearate, zinc stearate, silicone powder, polyethylene wax, and oxidized polyethylene wax.
5. The glass fiber reinforced composite plastic according to claim 1, characterized in that: Each portion of the synergistic agent comprises the following raw materials in parts by weight: 3-5 parts magnesium sulfate whiskers, 2-4 parts hyperbranched polyester, and 1-3 parts polycarbodiimide.
6. The glass fiber reinforced composite plastic according to claim 1, characterized in that: The catalyst is at least one of tetrabutyl titanate, tetraisopropyl titanate, and dibutyltin dilaurate.
7. The method for preparing glass fiber reinforced composite plastic according to any one of claims 1-6, characterized in that: The process includes the following steps: mixing raw materials, excluding glass fiber and silane coupling agent, in proportion; adding the mixed raw materials into the extruder through the main feed port; adding glass fiber, which has been pretreated with silane coupling agent, into the extruder through the side feed port; performing melt blending and granulation to obtain glass fiber reinforced composite plastic.
8. The method for preparing glass fiber reinforced composite plastic according to claim 7, characterized in that: The temperatures of each zone of the twin-screw extruder are as follows: The extruder is a twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are as follows: Zone 1: 220-230℃, Zone 2: 230-240℃, Zone 3: 230-240℃, Zone 4: 240-250℃, Zone 5: 235-245℃, and Die head: 235-2450℃. The side feed port is located in Zone 4.
9. The method for preparing glass fiber reinforced composite plastic according to claim 8, characterized in that: The screw speed of the twin-screw extruder is 200-400 rpm.
Citation Information
Patent Citations
PC / PEF alloy material containing bio-based polyester and preparation method thereof
CN108624024A
High-toughness low-floating-fiber reinforced PC / PBT alloy material and preparation method thereof
CN113462141A